ROAD SAFETY ENHANCEMENTS AND THEIR EFFECTS ON LOCAL COMMUNITIES: ANALYZING THE IMPACT OF ROAD SAFETY IMPROVEMENTS ON ACCIDENT REDUCTION AND QUALITY OF LIFE - Mohamad, Dadang (Ikatan Dosen Menulis, 2024)
This study analyzes the impact of road safety enhancements on local communities, focusing on accident reduction and quality of life improvements. It investigates how improved road infrastructure influences the frequency and severity of traffic accidents and assesses the broader socio-economic effects on residents. Using a mixed-methods approach, the research combines quantitative accident data with qualitative interviews from community members. The findings demonstrate significant reductions in traffic accidents and injuries, along with enhanced perceptions of safety and well-being among residents. Additionally, the study reveals improvements in community cohesion and economic activities due to safer roads. These insights provide valuable guidance for policymakers aiming to enhance urban safety and community welfare through infrastructure investments